2007
DOI: 10.1038/nchembio.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting metal ion–dependent folding and catalysis of a single DNAzyme

Abstract: Protein metalloenzymes use various modes for functions where metal-dependent global conformational change is required in some cases, but not in others. In contrast, most ribozymes appear to require a global folding that almost always precedes enzyme reactions. Herein we studied metal-dependent folding and cleavage activity of the 8-17 DNAzyme using single molecule fluorescence resonance energy transfer (FRET). Addition of Zn 2+ and Mg 2+ resulted in a folding step followed by cleavage reaction, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
142
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 42 publications
(49 reference statements)
5
142
0
Order By: Relevance
“…Being able to obtain the NaA43 DNAzyme with such a high selectivity for Na + will not only provide a highly selective sensor for Na + , as demonstrated here, it will also give us an opportunity to elucidate the origin of such a high selectivity. Previous studies of a Pb 2+ -DNAzyme have shown the high selectivity is mainly due to the DNAzyme forming a specific binding pocket for the metal ion (77). It would be interesting to find out if the NaA43 DNAzyme uses the same mechanism for selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to obtain the NaA43 DNAzyme with such a high selectivity for Na + will not only provide a highly selective sensor for Na + , as demonstrated here, it will also give us an opportunity to elucidate the origin of such a high selectivity. Previous studies of a Pb 2+ -DNAzyme have shown the high selectivity is mainly due to the DNAzyme forming a specific binding pocket for the metal ion (77). It would be interesting to find out if the NaA43 DNAzyme uses the same mechanism for selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, slow global conformational dynamics significantly impact the overall catalytic rate constant [23••-25]. Single molecule FRET also allowed for the dissection of the metal-ion dependent multi-step folding pathways of an in vitro selected Diels-Alderase ribozyme [26] and a DNAzyme [27]. Sometimes FRET can demonstrate the lack of significant conformational dynamics of a ribozyme, for example of the glmS ribozyme upon cofactor binding [18].…”
Section: Rna Catalysismentioning
confidence: 99%
“…19 At the same time, it is also studied as a model DNAzyme due to its recurrence in many different in vitro selections and high catalytic efficiency. [20][21][22][23][24][25] Examples of using the 8-17 DNAzyme for gene silencing are also known. 18,26 While many examples of DNAzyme-based intracellular mRNA cleavage are reported, 13 concerns have also been raised that the 10-23 DNAzyme is basically inactive with physiological concentrations of free Mg 2+ .…”
mentioning
confidence: 99%
“…For example, when an rAC junction was used, barely any cleavage was observed even with 500 mM Mg 2+ ( Figure S1, ESI). Therefore, it is also true for the [10][11][12][13][14][15][16][17][18][19][20][21][22][23] DNAzyme that its cleavage activity for every junction is not the same.…”
mentioning
confidence: 99%